Introduction. This Is Fine. Not - Isabel Bredenbröker (The February Journal)
This special issue investigates the potential of ‘hope,’ which is understood here as a future-oriented political practice. It combines critical perspectives on ‘hope’ with thinking about ‘problems.’ Contributions, which range from articles over conversations in written and spoken form to artistic text and imagery, add to sharpening the analytical usefulness of these ambiguous categories.